Image processing for TPEF/SHG laser scanning microscope - Tham, Yi Hui (2014)
Collagen is the most abundant protein in vertebrate animals. It makes up 25% to 35% of the whole-body protein content and plays important structural and functional roles in tissues and organs. For example, collagen can be generally found in connective tissues such as skin, tendon and ligament, providing strength and elasticity. Besides providing structural strength, it has been found that collagen there exist a relationship between collagen organization in tissue and its function. For example, imaging has shown that in normal tendons, collagen fibers are organized regularly. On the other hand, organization of collagen in injured tendons is random. Imaging of collagen has been developed to allow and enhance biological and medical research. Second harmonic generation (SHG) microscopy emerged as an established and powerful contrast mechanism for visualising fibrillar collagen in tissues. The disadvantage of this imaging method is that it has an extremely small field of view. In order to obtain meaningful information about collagens, a series of overlapping SHG images has to be captured to allow one to see the distribution of collagen. This project aims to design a MATLAB programme to process and stitch SHG images of collagen together effectively.